Lysine and methionine supplementation in isocaloric low protein diets on the performance of White Leghorn chicks* - BANDESWARN, C; PURUSHOTHAMAN, M R; RAVI, R (The Indian Journal of Animal Sciences, 2014)
Protein, lysine and methionine requirements for egger type White Leghorn chick were determined in a biological experiment for 8 weeks, using isocaloric (2600 Keal ME/kg) diets containing 20% protein, 19% protein+ Lys+Met, 19% protein, 18% protein+Lys+Met and 18% protein. There were nonsignificant differences in terms of body weight gain, total feed consumption, feed efficiency, blood parameters and carcass qualities among the treatment groups. Total nitrogen and uric acid nitrogen excretion were significantly lower and nitrogen retention was significantly higher in low protein fed groups. Lysine and methionic supplemention did not influence these parameters. This study revealed that 18% protein with 0.80% lysine and 0.34% methionine appear to be satisfactory for optimum performance of White Leghorn chicks in the cage system of rearing.